IMPROVING FARMERS EMPOWERMENT THROUGH TRAINING IN ORNAMENT PLANT SEED MANAGEMENT - dedi darmawan; nandang rukanda; sri nurhayati (IKIP Siliwangi Bandung, 2024)
Abstract The purpose of this research is to determine the process of empowering farmers through training in ornamental plant seed management in order to increase farmers' empowerment and ability, strength, and opportunity to develop and improve their quality of life. Qualitative research with a descriptive approach was used in this study. The participants include managers from the Community Learning Center (CLC) Suka Baru, tutors from the CLC Suka Baru, and learning citizens. The study employed field data analysis, which included data reduction, visualization, verification, and conclusion drawing. The findings indicated that: 1) Training planning is conducted in accordance with management procedures, beginning with the development of training instructions, validation, and implementation of training and evaluation programs. Tutors create Learning Implementation Plans (LIP) and schedule instructional materials. 2) The training conducted at CLC Suka Baru concluded successfully. This is demonstrated by the role of tutors, who communicate with and assist learners during training. Tutors deliver training in accordance with the planning that has been delivered and using simple-to-understand learning methods. Health protocols are used to conduct training via online and in-person meetings. 3) The training results indicate that learners improve their ability, knowledge, and understanding of ornamental plants to the point where they can learn how to sell online. This benefits agricultural businesses that manage plant seeds. Keywords: Farmers empowerment, Training, Community Learning Center